Substance use disorders in organ transplantation: perennial challenges and interprofessional opportunities. Issue 6 (27th December 2022) - Winder, Gerald S.; Clifton, Erin G.; Mellinger, Jessica L.
Abstract : Purpose of review: The current article examines recent publications regarding ongoing clinical and ethical challenges and opportunities related to substance use disorders (SUD) in solid organ transplantation (SOT) utilizing a lens of interprofessional clinical models and care delivery. Recent findings: Innovative interprofessional clinician skillsets and care models are increasingly emphasized in the SOT literature as the standard of care for common, complex psychosocial problems like substance use and SUD. Cannabinoids are common among candidates and recipients and present several unique quandaries to SOT teams. Opioid use disorder treatment can often be definitively treated with medications that SOT teams may find unfamiliar, controversial, or aversive. Arguably the quintessential example of SUD in SOT, early liver transplantation for patients with alcohol-related liver disease and short periods of sobriety has become increasingly common and accepted in recent years requiring liver teams to rapidly acquire significant interprofessional psychiatric awareness and expertise. The question of retransplantation in patients who have experienced recurrent SUD remains unsettled. Summary: Regardless of substances used or organs transplanted, interprofessional care continues to emerge as a foundational aspect of clinical care and research in SOT.